Bilingual identity negotiation in practice: teacher pedagogy and classroom interaction in a bilingual programme. Issue 2 (2nd April 2016) - Fielding, Ruth
Abstract : This paper discusses how teachers in a bilingual education programme see their pedagogies and interactions influencing student connection to the languages of the bilingual programme. The teacher perception of the classroom is explored because the classroom is one of the principal settings in which the students negotiate their bilingual identities. The students in this study were involved in two classroom settings within the same school in the Australian government school system. One setting was a so-called 'bilingual' classroom where two teachers were present – a native French speaker and a native English speaker – who each used their native language in a team-teaching setting; the other was an 'immersion' classroom where one native-speaker French teacher conducted the classes entirely in French. The paper explores the teachers' perceptions of their pedagogies and the co-teacher relationship as factors affecting student bilingual identity negotiation within the Bilingual Identity Negotiation Framework (BINF). This framework positions students' bilingual identity negotiation within the three intersecting spheres of socio-cultural connection, interaction and investment.